Cover Picture. Issue 3 (June 2015) - Unknown
<x xml:space="preserve">Abstract</x> The Chemical Record is an international and peer‐reviewed "highlights" journal publishing timely and critical overviews of new developments at the cutting edge of both core and interdisciplinary chemistry fields of interest to a wide audience of chemists. The Chemical Record provides carefully selected papers by leading researchers that introduce the author's own experimental and theoretical results in a framework designed to establish perspectives with earlier and contemporary work and provide a critical review of the present state of the subject.